1972
DOI: 10.1111/j.1469-185x.1972.tb00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death in Irradiated Adult Insects

Abstract: Summary 1. Irradiation of adult insects of many orders leads to their death. There is considerable evidence that such death occurs during a limited time period, both the beginning and duration of which are relatively independent of the dose over a wide range. This suggests the operation of a specific lethal syndrome. In other groups of insects, particularly Diptera and many moths, either the absence of somatic‐cell division or the short life of the imago prevents the development of this syndrome. These latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 115 publications
4
21
1
Order By: Relevance
“…The United States Food and Drug Administration has approved radiation doses up to 1,000 Gy (1 kGy) for preservation and disinfestation of fruits and vegetables (FDA 1986). Ionizing radiation breaks chemical bonds within DNA and other molecules, thereby disrupting normal cellular function in the infesting insect (Ducoff 1972, Koval 1994. Many tissues and functions of the insect may be disrupted by exposure to radiation (Vinson et al 1969, Nation andBurditt 1994).…”
mentioning
confidence: 98%
“…The United States Food and Drug Administration has approved radiation doses up to 1,000 Gy (1 kGy) for preservation and disinfestation of fruits and vegetables (FDA 1986). Ionizing radiation breaks chemical bonds within DNA and other molecules, thereby disrupting normal cellular function in the infesting insect (Ducoff 1972, Koval 1994. Many tissues and functions of the insect may be disrupted by exposure to radiation (Vinson et al 1969, Nation andBurditt 1994).…”
mentioning
confidence: 98%
“…This resistance has been attributed primarily to the lack of cell division in adult insects, in that the sensitivity of cells to irradiation is directly proportional to their reproductive activity (1)(2)(3), and because insects have minimal or no cell division in the adult state, they are extremely resistant to radiation (1,2).. Recent evidence has suggested that cells of insects have an intrinsic radioresistance (4).…”
mentioning
confidence: 99%
“…Consequently, eggs are normally the most susceptible life stage and adults are the most tolerant. Insect gonads and midgut contain mitotically active tissues, and irradiated insects are often sterile and stop feeding soon after treatment (Ducoff 1972;Tilton and Brower 1983;Koval 1994;Nation and Burditt 1994). The goal of a quarantine treatment is to prevent reproduction, and therefore the required response for a radiation treatment may be prevention of adult emergence (Follett and Armstrong 2004), or induction of adult sterility (Follett 2006a), or F 1 sterility (Follett 2006b(Follett , 2006c.…”
Section: Insect Radiotolerancementioning
confidence: 99%